Lecture Notes 10 - Function Operations and Inverses The...

This preview shows page 1 - 3 out of 10 pages.

We have textbook solutions for you!
The document you are viewing contains questions related to this textbook.
Elementary Algebra
The document you are viewing contains questions related to this textbook.
Chapter 1 / Exercise 5
Elementary Algebra
Tussy/Gustafson
Expert Verified
1
0
-1
1
9
9
9
We have textbook solutions for you!
The document you are viewing contains questions related to this textbook.
Elementary Algebra
The document you are viewing contains questions related to this textbook.
Chapter 1 / Exercise 5
Elementary Algebra
Tussy/Gustafson
Expert Verified
2g of()0( )=g(f(0)) = g 02()=g 0( )=0 – 3 =- 3g of()3( )=g(f(3)) = g 32()=g 9( )=9 – 3 =6g of()-1()=g(f(-1)) = g-1()2()=g 1( )=1 – 3 =- 2, and, in general,g of()x( )=g(f(x)) = g x2()=x2-3Notice that, for these two functions f and g, g of()x( )f og()x( )for any x value we tried,and they certainly are not generally equivalent. There is a value for whichg of()x( )=f og()x( ). Check out x = 2. You will find that g of()2( )=f og()2
The following examples should help.(2) For the two functions given above [f(x) = x + 1 and g(x) = 2x – 1],fog()x( )=f g x( )()= f2x -1()=2x -1()+1 =We’re basically substituting the formula for g(x), and then applying the rule for f on theresult.(3) Let f x( )=x2and g x( )=x – 3. Find f og()0( ), f og()3( ), f og()-1(), and f og()f og()0( )=f(g(0)) = f 0 – 3()=f-3()=-3()2=9f og()3( )=f(g(3)) = f 3 – 3()=f 0( )=0( )2=0f og()-1()=f(g(-1)) = f -1 – 3()=f-4()=-4()2=16, and, in general,f og()x( )=f(g(x)) = f x – 3()=x -3()2=x – 3()x – 3()=x2-6x +As with subtraction and division of functions, the order of composition is very important. Thenext example is chosen to illustrate this fact.(4) Let f x( )=x2and g x( )=x – 3. Find g of()0( ), g of()3( ), g of()-1(), and g of()2xx( ).,,9.x( ).
,
,
.
( ).

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture